Pengembangan Paket Strategi Pembelajaran Aktif - Supardi Supardi (JTP - Jurnal Teknologi Pendidikan, 2016)
This research is aimed at developing active learning tools to improve the effectiveness of the instructional strategy lectures at the Faculty of Teacher Training and Education of State Institute for Islamic Studies (FITK IAIN) Mataram. The method of this research is research and development (R&D) that was started with the process of needs assessment, the design of prototype of active learning tools that were tested in the next process by meansof expert validation, one to one, small groups, whole class, and effectiveness trials. The result of the trials on the developed product showed that its use had been effectively improved the students contribution during teaching and learning activities if compared to the students contribution in conventional learning process.